Inconstitucionalidad de la no aplicación del recurso de apelación al auto de llamamiento a juicio en el sistema jurídico penal de la República del Ecuador, y necesidad de reforma al Art. 343 numeral 1 del código de procedimiento penal. - Jiménez Gaona, Luis Fernando (2013)
The right to defense of all people is being violated by the inadequate application of legal regulations, especially in criminal law, on basic guarantees and due process that establishes the right to defense, Of the call to trial.